Stressful life events and difficulties and onset of breast cancer: case-control study - Protheroe, David (British Medical Journal, 1999)
OBJECTIVE: To determine the relation between stressful life events and difficulties and the onset of breast cancer. DESIGN: Case-control study. SETTING: 3 NHS breast clinics serving west Leeds. PARTICIPANTS: 399 consecutive women, aged 40-79, attending the breast clinics who were Leeds residents. MAIN OUTCOME MEASURES: Odds ratios of the risk of developing breast cancer after experiencing one or more severe life events, severe difficulties, severe 2 year non-personal health difficulties, or severe 2 year personal health difficulties in the 5 years before clinical presentation. RESULTS: 332 (83%) women participated. Women diagnosed with breast cancer were no more likely to have experienced one or more severe life events (adjusted odds ratio 0.91, 95% confidence interval 0.47 to 1.81; P=0.79); one or more severe difficulties (0.86, 0.41 to 1.81; P=0.69); a 2 year severe non-personal health difficulty (0.53, 0.12 to 2.31; P=0.4); or a 2 year severe personal health difficulty (2.73, 0.68 to 10.93; P=0.16) than women diagnosed with a benign breast lump. CONCLUSION: These findings do not support the hypothesis that severe life events or difficulties are associated with onset of breast cancer.